2016
DOI: 10.1038/nchembio.2045
|View full text |Cite
|
Sign up to set email alerts
|

Probes of ubiquitin E3 ligases enable systematic dissection of parkin activation

Abstract: E3 ligases represent an important class of enzymes, yet there are currently no chemical probes to profile their activity. We develop a new class of activity-based probe by reengineering of a ubiquitin-charged E2 conjugating enzyme and demonstrate their utility by profiling the transthiolation activity of the RING-in-between-RING (RBR) E3 ligase Parkin in vitro and in cellular extracts. Our study provides valuable insight into the roles, and cellular hierarchy, of distinct phosphorylation events in Parkin activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 60 publications
4
121
0
1
Order By: Relevance
“…We show the orientation of the phosphate group toward H68 and the R0RBR binding interface alters the autoinhibitory interaction and provides a rationale for the weakened affinity observed in trans (14,15,22). Further, our results add to the growing consensus that it is primarily the pUb signal that is responsible for the conformational change that relieves UBL-mediated autoinhibition (14,15,18,22,38). Although the specific order of phosphorylation events in cells remains controversial, parkin has evolved such that each phosphorylation signal induces a positive effect on activity and the receptors for each signal are physically distinct.…”
Section: Resultssupporting
confidence: 54%
“…We show the orientation of the phosphate group toward H68 and the R0RBR binding interface alters the autoinhibitory interaction and provides a rationale for the weakened affinity observed in trans (14,15,22). Further, our results add to the growing consensus that it is primarily the pUb signal that is responsible for the conformational change that relieves UBL-mediated autoinhibition (14,15,18,22,38). Although the specific order of phosphorylation events in cells remains controversial, parkin has evolved such that each phosphorylation signal induces a positive effect on activity and the receptors for each signal are physically distinct.…”
Section: Resultssupporting
confidence: 54%
“…While this manuscript was under review, two crystal structures of partially activated parkin appeared, which showed the pUbl domain has the ability to bind to the RING0 domain (Gladkova et al , 2018; Sauvé et al , 2018) comprised of a previously identified (Wauer & Komander, 2013) basic patch (K161, R163, K211) that included two ARJP substitutions. Mutation of these residues renders parkin unreactive with an E2‐based activity probe, consistent with a requirement for pUbl interaction (Pao et al , 2016). Yet other experiments show parkin retains appreciable ubiquitination ability in the absence of its Ubl domain (Chaugule et al , 2011; Kazlauskaite et al , 2014; Kumar et al , 2015), suggesting phosphorylation and the Ubl domain itself are less important.…”
Section: Discussionmentioning
confidence: 63%
“…This is supported by substitution of W403 that produces NMR chemical shift changes analogous to those for binding of UbcH7‐Ub. Further, experiments using an E2‐based activity probe show a W403A substitution can partially recapitulate catalytic cysteine labelling of parkin even in the absence of Ubl domain phosphorylation (Pao et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Such crosstalk is also exemplified by the recent and exciting revelation of the dual mitochondrial-ER origins of peroxisomes [53]. The development of next-generation chemical probes for monitoring Parkin-activation should also prove valuable in resolving the contribution of PINK1-Parkin signalling to these new and exciting aspects of mitochondrial cell biology [54]. Intriguing links between mitophagy and metabolic regulation are also emerging, especially with respect to cardiovascular development.…”
Section: Emerging Themes From Cell Biology To Pathologymentioning
confidence: 97%